Auditing cases - Knapp, Michael C (Thomson South-Westen, 2007)
The book contains case studies about audit including comprehensive cases, audits of high risk accounts, internal control issue, ethical responsibilities of accountants, ethical responsibilities of independent auditors, professional roles, professional issues and classic litigation cases